Influence of Chopstick Size on Taste Evaluations. Issue 2 (April 2015) - Lin, Hung-Ming; Lin, Chien-Huang; Hung, Hui-Hsi
This study explored the influence of the length of chopsticks on taste evaluations. Participants ( N = 78; M age = 21.1 yr., SD = 3.8) reported a greater liking for their food and higher purchase intentions when using long rather than short chopsticks. Findings also indicated that the long (vs short) chopsticks caused people to slow down when eating, resulting in greater eating duration and a higher number of mouthfuls. The findings of this study provide insights on research into the role of tableware in food intake.